O Comportamento Visual Exploratório dos Futebolistas aplicado ao Contexto Real de Prática: Relatório de Estágio Profissionalizante na União Desportiva de Sousense no escalão de juniores - Tiago Alberto Silva Oliveira (2018)
Soccer is becoming more competitive and the evolution of the modality happens because of two fundamental aspects. The first aspect, where the competitive character stands out is the physical capacity of athletes, capable of running high distances (allowing to cover more areas of the football field) and to achieve great relevance speeds to the game. The second aspect that promotes this ascending line, is that athletes are getting increasingly aware of the game and develop their cognitive skills for that. The way the game is quickly thought and processed in the athlete's head influence, in a decisive way, their competitiveness. The good reading of the game in symbiosis with one excellent decision making, allows the athlete to be successful in the sport. If we are able to help athletes improve these components, then we are collaborating for evolution of king of sports. The present report is based on the professional internship carried out in U. D. Sousense on the junior level in the season 2017/2018. The internship complements the second year of hight- perfomance sports training master's degree in the university of Oporto. During the internship has been realized a project about the decision making with focus on visual search behavior. Therefore, the work carried out in the U. D. Sousense intends to question if the athletes, more specifically the two most midfield used, perform visual search behaviour about positioning, moving colleagues and opponent, before they receive the ball and what the relationship is with they make the right or wrong decisions. For the analysis or these data were collected images of the games made by U.D. Sousense to perceive the regularity of the behaviors as well as their success or failure. The analysis was performed in two moments of evaluation. In first evaluation, athletes were unaware that they were being evaluated, and were given no information regarding the variables to be studied. After the first evaluation, an intervention plan was developed with the objective of improving the performance of the athletes in the analyzed components. The plan consisted of two exercises performed once a week over a period of 8 Weeks. In the second moment of evaluation, it was possible to identify significant improvements in the athletes' behavior.